A novel scheme of parameters control of microturbine system at different loading conditions. Issue 1 (2nd January 2020) - Rana, Vinaya; Ansari, M. A.; Chauhan, Yogesh K.; Tyagi, Arjun; Kumar, Krishan
Abstract: Controlling schemes for microturbine plays an important role on its performance. To control the various parameters of microturbine, the mathematical modeling of the system has been done. Permanent magnet synchronous generator is used for microturbine and modelled is done in d-q reference frame. An efficient power electronics interface has been used to change the high frequency into useful frequency range. The speed of the turbine is increased and decreased according to the load variation. The turbine is running on 100%, 90% and 80% of its rated speed. The turbine is connected to the different loads for analyzing its overall performance and controller. MATLAB/Simulation based microturbine system with PMSG has been developed to the analysis for the controlling of parameters. The system is tested on different loading conditions of 3 kW, 6.5 kW and 13 kW to obtained the optimize working of microturbine.